Factors Influencing Individual Involvement in Indonesia's Informal Economic Sectors - Syafitri, Wildan; Prestianawati, Silvi Asna; Fawwaz, Muhammad; Imamia, Tsumma Lazuardini; Rasli, Amran (International Journal of Social Science and Business, 2024)
This study aimed to investigate the factors influencing individuals to be involved in informal sectors in Indonesia. The factors include gender, marital status, age, education, migration, employment type, working hours, and income. Analyzing SAKERNAS 2020 data released by BPS using logistic regression method, this study found that all these factors have a significant influence on the employment sector (both informal and formal). The subjects’ characteristics such as being female, having particular marital status, aged over 40, educated at the senior high school level or lower, non-migrant status, involvement in agricultural business, working more than 8 hours a day, and earning a monthly income of 5 million rupiah, were found to influence individual preference of working in informal sectors. The study showed inequalities and gaps among individuals working in informal sectors in Indonesia, highlighting the need for the policymakers’ intervention to provide stimuli that can improve the welfare of informal economic actors and provide them with social protection.